Bicuspid Aortic Valve in Children and Adolescents: A Comprehensive Review - Gaia Spaziani; Francesca Girolami; Luigi Arcieri; Giovanni Battista Calabri; Giulio Porcedda; Chiara Di Filippo; Francesca Chiara Surace; Marco Pozzi; Silvia Favilli (Diagnostics, 2022)
Bicuspid aortic valve (BAV) is the most common congenital heart defect. Prevalence of isolated BAV in the general pediatric population is about 0.8%, but it has been reported to be as high as 85% in patients with aortic coarctation. A genetic basis has been recognized, with great heterogeneity. Standard BAV terminology, recently proposed on the basis of morpho-functional assessment by transthoracic echocardiography, may be applied also to the pediatric population. Apart from neonatal stenotic BAV, progression of valve dysfunction and/or of the associated aortic dilation seems to be slow during pediatric age and complications are reported to be much rarer in comparison with adults. When required, because of severe BAV dysfunction, surgery is most often the therapeutic choice; however, the ideal initial approach to treat severe aortic stenosis in children or adolescents is not completely defined yet, and a percutaneous approach may be considered in selected cases as a palliative option in order to postpone surgery. A comprehensive and tailored evaluation is needed to define the right intervals for cardiologic evaluation, indications for sport activity and the right timing for intervention.